Capturing, structuring and accessing design rationale in integrated product design and manufacturing processes. Issue 3 (August 2016) - Poorkiany, Morteza; Johansson, Joel; Elgh, Fredrik
Abstract: Developing customized products is the business case for many manufacturing companies striving to fulfill the customers' specific needs. When manufacturing customized products it is often necessary to also develop corresponding customized manufacturing tooling. There is a need to support concurrent development of new product variants along with their manufacturing toolsets. The communication between design engineers and manufacturing engineers is hence a key issue that if solved would enable design engineers to foresee how changes in product design affect tooling design and vice versa. To understand the correlation between the design of a product and its corresponding manufacturing tools, access to design rationale of the product and the developed tooling is required. Design rationale provides an explanation of why an artifact is designed in the way it is, including statements (textual, numerical or geometrical), argumentations, and decisions. Since design rationale is composed of information scattered all across the company's repositories in different formats (e.g. in type of a geometry, picture, table, and textual document), representing the design rationale is a challenge for many enterprises. In this paper a method is introduced that enables capture, structure and access to design rationale across product design and tooling design. The system enables representing design rationale in formats such as CAD models, spreadsheets, textual formats, and web pages. The method has been examined by developing a prototype system tested in a case company which develops and manufactures customized car accessories, such as roof racks and bike carriers, for different car models. The company develops and manufactures the products as well as the required tooling equipment. The prototype system includes different software commonly used by engineers during designing a product, for the purpose of making it applicable for other companies.